2019
DOI: 10.1080/13102818.2019.1649095
|View full text |Cite
|
Sign up to set email alerts
|

Improving blast resistance of the rice restorer line, Hui 316, by introducing Pi9 or Pi2 with marker-assisted selection

Abstract: Introducing resistance (R) genes into a susceptible rice cultivar is an effective strategy to achieve broad-spectrum and durable disease resistance. During the breeding process, marker-assisted selection (MAS) provides an efficient approach for direct screening of the progeny containing the R gene in a population. In this study, we designed an optimized polymerase chain reaction marker, Pi9/2, targeting the same polymorphic region of our previously developed Pi9-Pro and demonstrated that Pi9/2 is more specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Several studies have shown that MAS can efficiently monitor the introgression of blast resistance genes both into the recipient plants and improved varieties. For example, the Pi9/Pi92 gene was introgressed into the rice restorer line Hui 316 by Tian et al (2019). In the present study, we demonstrate the application of MAB in breeding to improve the blast resistance of an elite Malaysian rice variety, MR220 by transferring the Pi9 gene from a donor parent into the recipient variety.…”
mentioning
confidence: 58%
“…Several studies have shown that MAS can efficiently monitor the introgression of blast resistance genes both into the recipient plants and improved varieties. For example, the Pi9/Pi92 gene was introgressed into the rice restorer line Hui 316 by Tian et al (2019). In the present study, we demonstrate the application of MAB in breeding to improve the blast resistance of an elite Malaysian rice variety, MR220 by transferring the Pi9 gene from a donor parent into the recipient variety.…”
mentioning
confidence: 58%
“…Additionally, this technology has also made notable strides in rice breeding programs, where it has been used to identify markers associated with disease resistance, grain quality, and yield-related traits. For example, several studies have reported the successful use of KASP markers for identifying blast resistance genes, including Pi2 and Pi9 [20,21]. KASP markers have also been utilized to identify markers associated with other important diseases, such as bacterial blight [22] and bakanae disease [23].…”
Section: Discussionmentioning
confidence: 99%
“…In Chinese monogenic lines, the resistance to rice blast fungus was introduced in 2000. In fact, five resistant genes were introduced, via the conventional breeding techniques, into the blast susceptible Japonica rice variety named Lijiangxin-tuan-heigu (LTH) [ 40 , 41 ]. At the protein level, Pi9 is a member of the NBS-LRR genes that show broad-spectrum resistance to different rice blast strains.…”
Section: Discussionmentioning
confidence: 99%